Comprehensive modelling and sizing of PV systems from location to load. Issue 1771 (2015) - Isabella, O.; Nair, G. Ganesan; Tozzi, A.; Castro Barreto, J. Hernandez; Chandra Mouli, G. Ram; Lantsheer, F.; van Berkel, S.; Zeman, M.
ABSTRACT: Photovoltaic (PV) systems are progressively used for decentralized electricity generation. To obtain the maximum yield from such systems, optimisation of all components is essential. In this contribution, we provide a comprehensive modelling and sizing of PV systems for any location. Three applications are here presented providing real time monitoring of PV potential, accurate prediction of yield taking into account thermodynamic temperature effects, optimization of modules orientation addressing the effects of shading and efficient sizing of inverter for a higher yield output. When combined, these models can accurately predict the real time performance of any PV system.